Cultural Adaptation: The Impact of Social Media Toward Uses and Gratification - Mat Saad, Mohd Zuwairi; Yusuf, Mohd Hasren (Journal of Techno-Social, 2019)
The emergence of new media, the internet with various applications is used worldwide. It also alters the individual way of communicating and interacting with individuals with other individuals. With today’s technological advances, interaction between individuals does not just use texts but interaction relationships become more interactive with the existence of some social media. Various social media exist online like Instagram, Facebook, and others. These social media users are of different ages and backgrounds. The phenomenon of overwhelming social media poses many effects on the use of the internet as a new media as a result of the development of the technology itself. Through Theory of Uses and Satisfaction, individuals who use certain media and certain media content to meet their needs behind specific goals. The effects include on human communication. The facilities available on social media enable an individual to communicate with other individuals without boundaries as well as sharing information, knowledge, making friendships and being a medium to entertain. In addition, social media is also a medium of cultural adaptation. Adaptation between new cultures involves the process of understanding through interactions so that demands of a new cultural environment can be fulfilled. Keywords: communication, culture, social media, usability and satisfaction